Fabrication of nanostructures for surface-enhanced Raman scattering - Lu, Gang (2012)
Due to the wide application in the fields of physics, chemistry and biology, surface enhanced Raman scattering (SERS) attracted much attention in the past decades. Especially thanks to the development of nanoscience and nanotechnology, many SERS-active substrates have been fabricated using various techniques. In this thesis, several simple and convenient methods are developed to fabricate efficient SERS substrates. Moreover, a simple, convenient and flexible tool is developed for highly sensitive Raman detection. First, a simple and convenient method is developed for fabrication of SERS substrate by electroless deposition of Ag nanoparticles (NPs) on to catalytic etching-induced Si nanowells. The obtained Ag NP-coated Si nanowells show a dramatic Raman enhancement of the adsorbed p-aminothiophenol (PATP, Raman probe) molecules. After formation of sandwich nanostructures by adsorption of Au NPs on PATP-coated Ag NPs, the Raman enhancement increases further. Furthermore, the effect of the pore size and depth of Si nanowells as well as the size of Ag NPs coated on Si nanowells on Raman enhancement are systematically studied. Second, a simple, convenient and controllable method is developed to fabricate high-density Ag or Au nanogaps on Si wafer. These nanogaps can serve as Raman hot spots (an area in which extremely high Raman enhancement is attained), leading to a dramatic enhancement of Raman signals. The high-density nanogaps can be formed by repeating the electroless deposition of Ag NPs (or Au NPs) and the PATP monolayer coating on Ag NPs (or Au NPs) surface. After removal of PATP by O2 plasma, the as-fabricated SERS substrates are useful for detection of molecules. Third, a method is developed for fabrication of an efficient SERS substrate by combination of metallic nanostructures and graphene, which shows dramatic Raman enhancement and efficient adsorption of aromatic molecules. The fabricated Ag or Au NP-decorated reduced graphene oxide (rGO) on Si substrate is used as an efficient SERS substrate to detect the adsorbed aromatic molecules with low detection limit at nM level. Systematic studies on the effects of NP size and substrate morphology on Raman enhancement are presented. This method might be useful for the future application in detection of biomolecules, such as DNA and protein. Fourth, a simple but efficient method for highly sensitive Raman detection is proposed by covering a thin polydimethylsiloxane (PDMS) elastomer pre-coated with a layer of Au or Ag NPs onto the detected substrates, resulting in dramatic enhancement of Raman signals. Moreover, this NP-coated PDMS elastomer can be used for chemical imaging with high sensitivity. As a proof of concept, Raman mapping on the micropatterns of PATP and methylene blue are obtained.